A Bard in Search of The Lost Time: The Time and Memory Perception in Thomas Wolfe’s The Lost Boy - Akar, Mahmut (My University, 2018)
Thomas Wolfe is an American writer who usesautobiographical elements artfully in his works. Wolfe writes about theself-searching of Eugene Gant, the main character in The Lost Boy, who characterizes himself, Thomas Wolfe. The bookconsists of four parts. Each part contains a different family member'snarration about past and memories. During self- searching Eugene Gant benefitsfrom family photos, living spaces and even the slightest crumbs that animatememories. He tries to bring to light the memories, which were pushed intosubconscious, benefiting from narratives of family members. Time is a factorwhich pushes the memories into subconscious, makes them forget in this storywhere elements such as loss, loneliness, time flies, shape the leitmotif. Timeis also a factor bringing memories alive through different elements. In thisstudy Eugene Gant's reanimating of the memories by linking past to present willbe examined.

ThomasWolfe eserlerinde otobiyografik öğeleri ustaca kullanan Amerikalı bir yazardır.Thomas Wolfe, “The Lost Boy” adlı kısa hikAyesinde kendisini de karakterizeeden Eugene Gant’in öz arayışını incelemektir. Eser dört bölümündenoluşmaktadır. Her bölüm farklı bir aile bireyinin geçmiş zaman ve anılarınadair anlatımını içermektedir. Eugene Gant, öz arayışı esnasında; anılarınıcanlandıran aile fotoğraflarından, yaşanan mekAnlardan ve hatta en ufak anıkırıntılarından bile yararlanır. Aile bireylerinin anlatımlarından yararlanarakbilinçaltına itilen anıları gün yüzüne çıkarmaya çalışır. Ana temasınıyitiklik, yalnızlık, zamanın akıp gitmesi gibi unsurların şekillendirdiği buhikAyede zaman; anıları bilinçaltına iten, unutturan ve silip yok eden birunsurdur. Zaman, aynı zamanda, farklı etmenler aracılığı ile anılarıncanlanmasını sağlayan bir unsurdur. Bu çalışmada, Eugene Gant’in geçmiş zamanve şimdiyi bir birine bağlayarak anıları tekrardan canlandırmasıincelenecektir.
Yitik Zaman Peşinde Bir Ozan: Thomas Wolfe'un The Lost Boy Adlı Eserinde Zaman ve Anı Algısı
Keywords: Edebiyat